Effect of traction therapy on muscle satellite cell proliferation and differentiation in a rat model of knee stiffness - Xiaoqian Lv; Xiaoyu Wang; Jianxing Yue; Xin Wang; Haoyue Chen; Qiang Gao (Stem Cell Research & Therapy)
Abstract Background In the rat knee stiffness model, the duration of traction treatment is mostly 20–40 min; however, relatively few studies have been conducted on longer traction treatment of extended knee stiffness in rats. Therefore, the aim of this study was to explore the efficacy of prolonged traction and its mechanism of action in extended knee stiffness in rats. Methods The model of extended knee joint stiffness was established in rats and treated with powered flexion position traction. On the 10th and 20th days respectively, passive range of motion (PROM) assessments and musculoskeletal ultrasound were conducted. Rectus femoris muscle tissues were taken for Western blotting (WB) to detect the expression of muscle satellite cells proliferation and differentiation signaling factors. Histopathological staining was used to evaluate the degree of muscle atrophy and muscle fibrosis in the rectus femoris muscle, and immunofluorescence double staining was used to detect proliferation of muscle satellite cells number. The results from these analyses were used to assess the therapeutic outcomes of the traction treatment. Results The findings indicated that chronic persistent traction significantly improved joint mobility, notably enhanced the proliferation of muscle satellite cells, and inhibited their differentiation. Furthermore, the treatment facilitated the repair and regeneration of damaged tissues, reduced muscular atrophy and fibrosis in the rectus femoris muscle, and alleviated knee stiffness. Conclusion Chronic persistent traction can effectively relieve knee joint stiffness, and its mechanism is related to the activation and proliferation of the rectus femoris muscle satellite cells, thereby promoting the repair and regeneration of damaged skeletal muscle.